Metal protoporphyrin‐induced self‐assembly nanoprobe enabling precise tracking and antioxidant protection of stem cells for ischemic stroke therapy. Issue 1 (14th February 2023) - Shu, Yimeng; Shen, Hui; Yao, Minghua; Shen, Jie; Yang, Guo‐Yuan; Chen, Hangrong; Tang, Yaohui; Ma, Ming
Abstract: Mesenchymal stem cell (MSC)‐based therapy has provided a promising strategy for the treatment of ischemic stroke, which is still restricted by the lack of long‐term cell tracking strategy as well as the poor survival rate of stem cells in ischemic region. Herein, a dual‐functional nanoprobe, cobalt protoporphyrin‐induced nano‐self‐assembly (CPSP), has been developed through a cobalt protoporphyrin IX (CoPP) aggregation‐induced self‐assembly strategy, which combines CoPP and superparamagnetic iron oxide (SPION) via a simple solvent evaporation‐driven method. Without any additional carrier materials, the obtained CPSP is featured with good biocompatibility and high proportions of active ingredients. The SPIONs in CPSPs form a cluster‐like structure, endowing this nano‐self‐assembly with excellent T2 ‐weighted magnetic resonance (MR) imaging performance. Furthermore, the CoPP released from CPSPs could effectively protect MSCs by upregulating heme oxygenase 1 (HO‐1) expression. The in vivo cell tracing capacity of CPSPs is confirmed by monitoring the migration of labeled MSCs with MR imaging in a middle cerebral artery occlusion mouse model. More importantly, the sustained release of CoPP from CPSPs improves the survival of transplanted MSCs and promotes neural repair and neurobehavioral recovery of ischemic mice. Overall, this work presents a novel dual‐functional nanoagent with an ingenious design for advancing MSC‐based therapy. Abstract : A novel cobalt protoporphyrin‐induced nano‐self‐assembly (CPSP) with magnetic resonance (MR) imaging and antioxidative protection dual‐functions is ingeniously constructed for advancing stem cell therapy. CPSP labeled stem cells can not only be tracked in vivo by MR imaging, but also survive longer in the ischemic lesions, thus achieving improved therapeutic effect in ischemic stroke.